Profound Hypercalcemia Associated with Acute Toxic-Metabolic Encephalopathy After Calcium Sulfate Bead Use: A Case Report. Issue 1 (January 2022) - Sabharwal, Samir; Schmerler, Jessica; Thakkar, Savyasachi C.
Abstract : Case: We present the case of an 81-year-old woman who developed profound hypercalcemia requiring admission to the intensive care unit after calcium sulfate bead use during revision hip arthroplasty. The patient's serum calcium level peaked at 21.0 mg/dL and was associated with acute encephalopathy. After treatment with calcitonin and bisphosphonates, her serum calcium level normalized and her mentation improved. Conclusion: The risk of clinically significant hypercalcemia should be considered when using calcium sulfate during orthopaedic surgery.